THE CHANGING IDEA OF HIGHER EDUCATION - Holubek, Vesna (The Modern Higher Education Review, 2018)
Questions concerning the purpose and the nature of higher education are often referred to as “the idea of higher education”. The article illustrates that the idea of higher education is contextual and changeable, thus contested over time. The aim of the article is to present and analyse some of the most prominent changes in the idea of higher education last three decades by reviewing relevant literature. The analysis focuses on three major influences that redefine the idea of higher education in Europe – massification, globalisation and internationalisation, and neoliberal ideas. The recognised changes transform the way higher education is understood and conceptualised which in turn affects the way higher education is organised and developed in practice.